Enhancing Vocabulary and Listening Comprehension Skills in Children with Limited Language Proficiency: The Impact of Dialogic Reading Interventions - Bilge Nur Dogan Guldenoglu (SAGE Open)
This study aimed to examine the impact of dialogic reading implemented within a classroom setting on the vocabulary and listening comprehension skills of kindergarten children defined as children with limited language proficiency. The study enlisted a cohort of 61 kindergarten participants sourced from classes in Ankara, Turkey. A classroom-based dialogic reading intervention was administered over 12 weeks, with two sessions per week, each lasting two hours. Pre and post-test assessments were conducted using the Turkish Test of Early Literacy (TEL) to gauge participants' vocabulary and listening comprehension skills. Results revealed a noticeable enhancement in both vocabulary acquisition and listening comprehension skills subsequent to the dialogic book reading intervention. Statistical analyses unveiled significant disparities between pre and post-test scores across all sub-dimensions related to participants' vocabulary and listening comprehension skills. This study contributes to the growing body of experimental literature, affirming that the integration of dialogic reading interventions within a classroom environment significantly enhances the vocabulary and listening comprehension skills of young children from academically disadvantaged backgrounds. Furthermore, the findings emphasize the critical role of demonstrating that dialogic reading interventions, particularly those grounded in real-life experiences and practical classroom applications, significantly enhance children's foundational language skills. This highlights the practical relevance of such well-structured interventions, offering important insights for their implementation in future educational practices.